2017
DOI: 10.1080/02640414.2017.1322215
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-motor dual-task ability of athletes with and without intellectual impairment

Abstract: Cognition is important in many sports, for example, making split-second-decisions under pressure, or memorising complex movement sequences. The dual-task (DT) paradigm is an ecologically valid approach for the assessment of cognitive function in conjunction with motor demands. This study aimed to determine the impact of impaired intelligence on DT performance. The motor task required balancing on one leg on a beam, and the cognitive task was a multiple-object-tracking (MOT) task assessing dynamic visual-search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…There was no significant difference in EF between males and females RA. EF performance was the highest among the age group (18)(19)(20)(21)(22)(23)(24) population, but in (25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and (35)(36)(37)(38)(39)(40) had comparable results in EF and DTE. Our study concluded that multiple types and levels of participation in recreational sport activity are useful in maintaining high levels of EF performance for the RA population, between 18-40 years of age.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…There was no significant difference in EF between males and females RA. EF performance was the highest among the age group (18)(19)(20)(21)(22)(23)(24) population, but in (25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and (35)(36)(37)(38)(39)(40) had comparable results in EF and DTE. Our study concluded that multiple types and levels of participation in recreational sport activity are useful in maintaining high levels of EF performance for the RA population, between 18-40 years of age.…”
Section: Discussionmentioning
confidence: 89%
“…Second outcome measure is DTI measured using the traditional formula for evaluating the DTE on a particular outcome of interest 38) : DTE (%)=(DT gait speed − single task gait speed) / single task gait speed × 100% 39) Negative percentage was defined as "worsened performance" in DT conditions while a positive percentage reflected "better performance" in DT conditions. DT paradigm is an ecologically valid approach for the assessment of cognitive function in conjunction with motor demands 40) . Data collection was carried out by a licensed physiotherapist and a senior PT student under the direction of the primary investigator.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…The athletes with ID score lower on the concentration disruption subscale compared to athletes without ID. This finding might be related to the increased need for athletes with ID to invest more actively in concentrating on their sports performance, as it might be less automatized and internalized compared to athletes without ID (Van Biesen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Dual-tasking creates a more realistic testing environment, as it resembles the actual context of sport, where two or more tasks are performed simultaneously at all times (e.g., maintaining optimal speed and proper technique while judging the appropriate time to initiate the turning point in swimming). While executing two or more task simultaneously, the brain needs to constantly decide how to allocate the available cognitive resources, and as individuals with II have limited cognitive resources, this is expected to be more challenging compared to athletes without II (Mikolajczyk & Jankowicz-Szymanska, 2015;Van Biesen, Jacobs et al, 2017).…”
Section: Enhancing the Quality Of Evidence-based Classificationmentioning
confidence: 99%